Characterization of Progenitor Cells during Canine Retinal Development - Mallely Ávila-García; Gustavo García-Sánchez; Esmeralda Lira-Romero; Norma Moreno-Mendoza (Stem Cells International)
We identify the presence of progenitor cells during retinal development in the dog, as this species represents a natural model for studying several breed-specific degenerative retinal disorders. Antibodies to detected progenitor cells (Pax6, C-kit, and nestin) and ganglion cells (BDNF, Brn3a, and Thy1) were used in combination with H3 for the purpose of identifying proliferating cells. Pax6, nestin, C-kit, and H3 were localized mainly in the neuroblastic layer of the retina during the embryonic stage. During the fetal stage, proteins were expressed in the inner neuroblastic layer (INL) as well as in the outer neuroblastic layer; BDNF, Thy1, and Brn3a were also expressed in the INL. During the neonatal stage only C-kit was not expressed. Proliferating cells were present in both undifferentiated and differentiated retina. These results suggest that, during canine retinogenesis, progenitor cells are distributed along the retina and some of these cells remain as progenitor cells of the ganglion cells during the first postnatal days.